Animal Tracking Telemetry Circuit using Low Power FM Transmitter - Al Hadi, Md. Abdullah (Engineering International, 2016)
There are many rare animals in every countries. Like here in Bangladesh Royal Bengal Tiger is one of them. They need to be protected from being disappeared. Detail information such as their number or their location is also necessary to be collected as they are our national resource. So in this project, a wireless telemetry circuit for animal tracking will be designed, built and tested.  The project includes a tone generator, a Low power FM transmitter, and a Spectrum Analyzer. The purpose is to help scientist track and locate animals by sending and receiving radio wave pulses from the FM Transmitter attached to the animal.
Keywords: Tone Generator; FM Transmitter; Spectrum Analyzer